(untitled) (Emergency Care Journal, 2018)
The prevalence of syncope increases with advancing age and is associated with significant morbidity and mortality. The diagnosis within this population can be complex due to atypical presentations, amnesia for events, absence of witnesses and the overlap with other clinical presentations, as falls. The recent reappraisal of the European Society of Cardiology guidelines on syncope, proposes a structured assessment and management, which is enforceable also in the older patient, with special attention to some additional features, pertinent to age-related comorbidity and frailty.